Identifying the core competencies of backup nurses in the acute care hospital through a modified Delphi process† - Feng Yan-Ying; Shi Guang; Huang Xi-Mei (Sciendo, 2022)
The backup nurses are created to meet emergencies in the case of inadequate nursing staff and emergency circumstances, and there are no clear definitions of the core competencies for training and evaluation of backup nurses in the acute care hospitals in China.